Moderskab og feminisme - Belyst ud fra enemorfamilien - Bak, Maren (Kvinder, Køn & Forskning, 1997)
Feminism’s relationship to maternity as a part of women’s lives has been marked by ambivalence and doubt. Feminist analyses has concentrated on maternity as a sphere for socialpolitical intervention and on the cultural representations of motherhood. But maternity as part of almost every womans life and lived expericence has been seen by feminists as a major arena for patriarchal oppression and reproduction of traditional gender roles and therefore analysed with doubt and distrust. In the article I argue for the need for a feminist research on the phenomenology of maternity. The empirical investigation of family strategies and maternity in 25 Danish single mother families, carried out by the author, showed an example of maternity as a base for autonomy and selfdetermination. The single mothers emphasized that their children and their work was their basis in life. Maternity was a source of pride and empowement for the mothers. The possibility to make their own decisions regarding themselves and their children was mentioned as a major advantage. The single mother’s experiences raise the question if maternity as autonomy and selfreliance is only possible outside two parent relationship. The author argues, that this is not the case, but the development of a nurturing fatherhood which takes repronsibility for nuturing values both in private life and in relationship to the labour market and social policy is a prerequisite.